Corrigendum to ‘Corenet: A flexible framework for generating and prioritising core cycle network designs’ [Journal of Transport Geography 122 (2026) 104148] - Zhao Wang; Hang Hu; Hussein Mahfouz; Juan Pablo Fonseca-Zamora; Martin Lucas-Smith; Dustin Carlino; Angus Calder; Congying Hu; Matthew Davis; Joseph Talbot; Robin Lovelace (Journal of Transport Geography, 2026)

Corenet: A flexible framework for generating and prioritising core cycle network designs - Zhao Wang; Hang Hu; Hussein Mahfouz; Juan Pablo Fonseca-Zamora; Martin Lucas-Smith; Dustin Carlino; Angus Calder; Congying Hu; Matthew Davis; Joseph Talbot; Robin Lovelace (Journal of Transport Geography, 2026)

Ancient bears provide insights into Pleistocene ice age refugia in Southeast Alaska - Flavio Augusto da Silva Coelho; Stephanie Gill; Crystal M. Tomlin; Marilena Papavassiliou; Sean D. Farley; Joseph A. Cook; Sarah A. Sonsthagen; George K. Sage; Timothy H. Heaton; Sandra L. Talbot; Charlotte Lindqvist (Molecular Ecology, 2023)
During the Late Pleistocene, major parts of North America were periodically covered by ice sheets. However, there are still questions about whether ice‐free refugia were present in the Alexander Archipelago along the Southeast (SE) Alaska coast during the last glacial maximum (LGM). Numerous subfossils have been recovered from caves in SE Alaska, including American black ( Ursus americanus ) and brown ( U. arctos ) bears, which today are found in the Alexander Archipelago but are genetically distinct from mainland bear populations. Hence, these bear species offer an ideal system to investigate long‐term occupation, potential refugial survival and lineage turnover. Here, we present genetic analyses based on 99 new complete mitochondrial genomes from ancient and modern brown and black bears spanning the last ~45,000 years. Black bears form two SE Alaskan subclades, one preglacial and another postglacial, that diverged >100,000 years ago. All postglacial ancient brown bears are closely related to modern brown bears in the archipelago, while a single preglacial brown bear is found in a distantly related clade. A hiatus in the bear subfossil record around the LGM and the deep split of their pre‐ and postglacial subclades fail to support a hypothesis of continuous occupancy in SE Alaska throughout the LGM for either species. Our results are consistent with an absence of refugia along the SE Alaska coast, but indicate that vegetation quickly expanded after deglaciation, allowing bears to recolonize the area after a short‐lived LGM peak.

Climate‐driven spatial and temporal patterns in peatland pool biogeochemistry - Julien Arsenault; Julie Talbot; Lee E. Brown; Manuel Helbig; Joseph Holden; Jorge Hoyos‐Santillan; Émilie Jolin; Roy Mackenzie; Karla Martinez‐Cruz; Armando Sepulveda‐Jauregui; Jean‐François Lapierre (Global Change Biology, 2023)
Peatland pools are freshwater bodies that are highly dynamic aquatic ecosystems because of their small size and their development in organic‐rich sediments. However, our ability to understand and predict their contribution to both local and global biogeochemical cycles under rapidly occurring environmental change is limited because the spatiotemporal drivers of their biogeochemical patterns and processes are poorly understood. We used (1) pool biogeochemical data from 20 peatlands in eastern Canada, the United Kingdom, and southern Patagonia and (2) multi‐year data from an undisturbed peatland of eastern Canada, to determine how climate and terrain features drive the production, delivering and processing of carbon (C), nitrogen (N), and phosphorus (P) in peatland pools. Across sites, climate (24%) and terrain (13%) explained distinct portions of the variation in pool biogeochemistry, with climate driving spatial differences in pool dissolved organic C (DOC) concentration and aromaticity. Within the multi‐year dataset, DOC, carbon dioxide (CO 2 ), total N concentrations, and DOC aromaticity were highest in the shallowest pools and at the end of the growing seasons, and increased gradually from 2016 to 2021 in relation to a combination of increases in summer precipitation, mean air temperature for the previous fall, and number of extreme summer heat days. Given the contrasting effects of terrain and climate, broad‐scale terrain characteristics may offer a baseline for the prediction of small‐scale pool biogeochemistry, while broad‐scale climate gradients and relatively small year‐to‐year variations in local climate induce a noticeable response in pool biogeochemistry. These findings emphasize the reactivity of peatland pools to both local and global environmental change and highlight their potential to act as widely distributed climate sentinels within historically relatively stable peatland ecosystems.

Whole‐genome resequencing reveals persistence of forest‐associated mammals in Late Pleistocene refugia along North America’s North Pacific Coast - Jocelyn P. Colella; Tianying Lan; Sandra L. Talbot; Charlotte Lindqvist; Joseph A. Cook (Journal of Biogeography, 2021)
Aim Numerous glacial refugia have been hypothesized along North America's North Pacific Coast that may have increased divergence of refugial taxa, leading to elevated endemism and subsequently clustered hybrid zones following deglaciation. The locations and community composition of these ice‐free areas remains controversial, but whole‐genome sequences now enable detailed analysis of the demographic and evolutionary histories of refugial taxa. Here, we use genomic data to test spatial and temporal processes of diversification among martens with respect to the Coastal Refugium Hypothesis, to understand the role of climate cycling in shaping diversity across complex landscapes. Location North America and North Pacific Coast archipelagos. Taxon North American martens ( Martes ). Methods Short‐read whole‐genome resequencing data were generated for 11 martens: four M. americana , four M. caurina , two hybrids, and one outgroup ( Martes zibellina ). Sampling was representative of known genetic clades within New World martens, including sampling within insular and continental hybrid zones and along the North Pacific Coast (five island populations). ADMIXTURE , F‐statistics, and D ‐statistics (ABBA‐BABA) were used to identify introgression and infer directionality. Heterozygosity densities, estimated via PSMC, were used to characterize historical demography at and below the species level to infer refugial and colonization processes. Results Forest‐associated Pacific martens ( M. caurina ) are divided into distinct insular and continental clades consistent with the Coastal Refugium Hypothesis. There was no evidence of introgression on islands that received historical translocations of American pine martens ( M. americana ), but introgression was detected in two active zones of secondary contact: one insular and one continental. Only early‐generational hybrids were identified across multiple hybrid zones, a pattern consistent with potential genetic swamping of M. caurina by M. americana . Main conclusions Despite an incomplete fossil record, genomic evidence supports the persistence of forest‐associated martens, likely the insular Pacific marten lineage, along the western edges of the Alexander Archipelago during the Last Glacial Maximum. This discovery informs our understanding of refugial paleoenvironments, critical to interpreting refugial timing, duration, and community composition. Genomic reevaluations of other taxa along North America's North Pacific Coast may yield new and deeper perspectives on the history of refugial forest communities and the role of dynamic climate shifts in shaping high‐latitude diversity across complex insular landscapes.

A response to “Media representation of hemlock woolly adelgid management risks: a case study of science communication and invasive species control,” published in biological invasions online on September 18, 2018 - Scott M. Salom; Gina Davis; Joseph Elkinton; Jeremiah Foley; Nathan Havill; Carrie Jubb; Albert Mayfield; Tom McAvoy; Rusty Rhea; R. Talbot Trotter; Mark Whitmore (Biological Invasions, 2019)

Implications of introgression for wildlife translocations: the case of North American martens - Jocelyn P. Colella; Robert E. Wilson; Sandra L. Talbot; Joseph A. Cook (Conservation Genetics, 2019)

A multilocus evaluation of ermine ( Mustela erminea ) across the Holarctic, testing hypotheses of Pleistocene diversification in response to climate change - Natalie G. Dawson; Andrew G. Hope; Sandra L. Talbot; Joseph A. Cook (Journal of Biogeography, 2014)
Aim We examined data for ermine ( M ustela erminea ) to test two sets of diversification hypotheses concerning the number and location of late P leistocene refugia, the timing and mode of diversification, and the evolutionary influence of insularization. Location Temperate and sub‐ A rctic N orthern H emisphere. Methods We used up to two mitochondrial and four nuclear loci from 237 specimens for statistical phylogeographical and demographic analyses. Coalescent species‐tree estimation used a Bayesian approach for clade divergence based on external mutation rate calibrations. Approximate Bayesian methods were used to assess population size, timing of divergence and gene flow. Results Limited structure coupled with evidence of population growth across broad regions, including previously ice‐covered areas, indicated expansion from multiple centres of differentiation, but high endemism along the N orth P acific coast ( NPC ). A bifurcating model of diversification with recent growth spanning three glacial cycles best explained the empirical data. Main conclusions A newly identified clade in N orth A merica indicated a fourth refugial area for ermine. The shallow coalescence of all extant ermine reflects a recent history of diversification overlying a deeper fossil record. Post‐glacial colonization has led to potential contact zones for multiple lineages in north‐western N orth A merica. A model of diversification of ermine accompanied by recent gene flow was marginally less well supported than a model of divergence of major clades in response to the most recent glacial cycles.

Temporal, spatial and ecological dynamics of speciation among amphi‐ B eringian small mammals - Andrew G. Hope; Naoki Takebayashi; Kurt E. Galbreath; Sandra L. Talbot; Joseph A. Cook (Journal of Biogeography, 2013)
Aim Quaternary climate cycles played an important role in promoting diversification across the N orthern H emisphere, although details of the mechanisms driving evolutionary change are still poorly resolved. In a comparative phylogeographical framework, we investigate temporal, spatial and ecological components of evolution within a suite of H olarctic small mammals. We test a hypothesis of simultaneous divergence among multiple taxon pairs, investigating time to coalescence and demographic change for each taxon in response to a combination of climate and geography. Location Beringia, the nexus of the northern continents. Methods We used approximate B ayesian computation methods to test for simultaneous divergence among eight pairs of taxa, using cytochrome b gene sequences. We calculated coalescence times for eastern and western components of each pair and for the combined pairs, and relate dates to Q uaternary climatic periodicity and combinations of environmental events and physical barriers. Population growth and expansion statistics were used to test evolutionary responses among taxa, including range shifts, persistence or periodic extirpation. Species distribution models ( SDM s) for each taxon were used to predict their geographical ranges during the present interglacial, L ast G lacial M aximum and previous interglacial. Results Multiple divergence events across B eringia were primarily coincident with extreme glacial cycles of the late Q uaternary. Structure within B eringia is spatially consistent with at least three environmental barriers arising at different times: the K olyma U plands, B ering S trait and portions of the B ering I sthmus. Levels of divergence varied substantially, indicating evolutionary processes spanning deep and shallow time‐scales. The different demographics among taxa reflect their distinct ecological responses. SDM s predicted regional distributional changes through time and different spatial responses among taxa. Main conclusions Beringia predominantly constituted a dispersal corridor during the early Q uaternary and a major centre of endemism in the late Q uaternary. Coincident with severe glacial cycles, small mammal species were ‘caught’ in B eringia and diversified over multiple climatic phases. Relative genetic differentiation across B eringia appears to be related to ecological differences reflecting a gradual adaptation to B eringian environments through time. Some methodological constraints associated with resolving recent (late Q uaternary) isolation events or drawing inferences from a single locus are discussed.

A Signal for Independent Coastal and Continental histories among North American wolves - BYRON V. WECKWORTH; SANDRA TALBOT; GEORGE K. SAGE; DAVID K. PERSON; JOSEPH COOK (Molecular Ecology, 2005)
Relatively little genetic variation has been uncovered in surveys across North American wolf populations. Pacific Northwest coastal wolves, in particular, have never been analysed. With an emphasis on coastal Alaska wolf populations, variation at 11 microsatellite loci was assessed. Coastal wolf populations were distinctive from continental wolves and high levels of diversity were found within this isolated and relatively small geographical region. Significant genetic structure within southeast Alaska relative to other populations in the Pacific Northwest, and lack of significant correlation between genetic and geographical distances suggest that differentiation of southeast Alaska wolves may be caused by barriers to gene flow, rather than isolation by distance. Morphological research also suggests that coastal wolves differ from continental populations. A series of studies of other mammals in the region also has uncovered distinctive evolutionary histories and high levels of endemism along the Pacific coast. Divergence of these coastal wolves is consistent with the unique phylogeographical history of the biota of this region and re‐emphasizes the need for continued exploration of this biota to lay a framework for thoughtful management of southeast Alaska.